2D and 3D in-situ mechanical testing of an interpenetrating metal ceramic composite consisting of a slurry-based ceramic foam and AlSi10Mg. (1st May 2021) - Schukraft, Joél; Lohr, Christoph; Weidenmann, Kay André
Abstract: An interpenetrating metal ceramic composite, based on a ceramic foam and an AlSi10Mg light-weight aluminum alloy, is investigated under compressive load. The ceramic preform is produced by mechanical stirring, drying and finally sintering. It has a relative density of approximately 25% and is infiltrated via gas-pressure infiltration with the aluminum alloy. The damage processes during compressive load, as well as an understanding of crack development is in focus of this research and obtained by complementing 2D and 3D characterization methods. Therefore, a 2D surface in-situ investigation setup with an universal testing machine, a digital image correlation and a microscopy setup is used. For 3D investigation, a compression test with an in-situ X-ray computed tomography is developed and carried out to get an understanding of the material crack growth and crack propagation, as well as its failure mechanisms inside the interpenetrating metal-ceramic phase composite. The material shows crack initiations in the ceramic phase parallel to the load direction. Formation of crack clusters is followed then by a change in failure mechanism due to shear stress dominated failure with a macroscopic crack in 45° regarding the load direction. A good-natured failure of the composite could be determined. The combination of the 2D and 3D investigation methods gives an insight into the failure behavior of the interpenetrating composite and thus contributes to the understanding of the failure mechanism beyond the current state of knowledge.